STRATEGI CAMAT DALAM MENINGKATKAN DISIPLIN KERJA PEGAWAI - Wayudin Sunubi; Parman Parman (Program Studi Ilmu Pemerintahan, Universitas Muhammadiyah Kendari, 2021)
This research was conducted to determine the subdistrict head's strategy on the level of employee discipline at the Ranomeeto Barat Subdistrict Office, South Konawe Regency. The method used in this study was a qualitative descriptive method. Data was collected through observation, interviews and literature study. Research informants were selected purposively with the intention that the selected informants knew the research problem. The informants in this study were the secretary of the West Ranomeeto District, three Government Sections and three people. The results showed that the sub-district head's strategy in improving employee discipline has been going well, it can be seen in the achievement of the outcome indicators, namely the ability to manage resources, emphasis on ethics and organizational control, the results of which show that each indicator has met employee performance standards with the aim of creating discipline.